POTENSI PATI KENTANG (SOLANUM TUBEROSUM) SEBAGAI BAHAN EDIBLE FILM RAMAH LINGKUNGAN UNTUK KEMASAN PANGAN - Panjaitan, Khayla Utami Sapta; Abdurrachman, Aryoko (Smart Education, 2025)
Abstract: The increasing use of conventional plastic packaging in the food industry has led to serious environmental problems due to its low biodegradability. This condition encourages the development of alternative packaging materials that are environmentally friendly, renewable, and safe for food contact. One potential natural material is potato starch (Solanum tuberosum), which is abundantly available and has suitable physicochemical properties for edible film production. This study aims to systematically review the potential of potato starch as a raw material for environmentally friendly edible films used in food packaging. The research employed a literature review method by analyzing relevant national and international scientific publications, statistical reports, and previous studies related to potato starch characteristics, edible film production, and their applications. The results indicate that potato starch, with a starch content ranging from 15–28%, contains amylose and amylopectin that support the formation of stable film matrices. The presence of resistant starch type 2 contributes to improved film homogeneity and mechanical stability. The edible film production process is relatively simple, involving starch extraction, gelatinization, plasticizer addition, and drying. Potato starch–based edible films show strong potential for use as biodegradable food packaging, such as dry food wrappers and protective coatings for fresh products.Keywords: potato starch, edible film, biodegradable packaging, food packaging, sustainable materials Abstrak: Penggunaan plastik konvensional dalam industri pangan telah menimbulkan permasalahan lingkungan yang semakin serius akibat sifatnya yang sulit terurai secara alami. Kondisi ini mendorong perlunya pengembangan bahan kemasan alternatif yang ramah lingkungan, dapat diperbarui, dan aman untuk kontak langsung dengan pangan. Salah satu bahan alami yang berpotensi adalah pati kentang (Solanum tuberosum), yang tersedia melimpah dan memiliki karakteristik fisikokimia yang mendukung pembentukan edible film. Penelitian ini bertujuan untuk mengkaji secara sistematis potensi pati kentang sebagai bahan dasar edible film ramah lingkungan untuk kemasan pangan. Metode yang digunakan adalah kajian literatur dengan menganalisis berbagai publikasi ilmiah nasional dan internasional, laporan statistik, serta hasil penelitian terdahulu yang relevan. Hasil kajian menunjukkan bahwa pati kentang memiliki kandungan pati sebesar 15–28% dengan komposisi amilosa dan amilopektin yang mendukung pembentukan matriks film yang stabil. Keberadaan pati resisten tipe 2 berkontribusi terhadap homogenitas dan kestabilan struktur film. Proses pembuatan edible film berbasis pati kentang tergolong sederhana, meliputi ekstraksi pati, gelatinisasi, penambahan plasticizer, dan pengeringan. Edible film berbasis pati kentang berpotensi diaplikasikan sebagai kemasan pangan biodegradable, seperti pembungkus makanan kering dan pelapis produk segar.Kata kunci: pati kentang, edible film, kemasan biodegradable, kemasan pangan, bahan berkelanjutan